2007
DOI: 10.1103/physreva.76.053831
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing potential energy functions for maximal intrinsic hyperpolarizability

Abstract: We use numerical optimization to study the properties of (1) the class of one-dimensional potential energy functions and (2) systems of point charges in two-dimensions that yield the largest hyperpolarizabilities, which we find to be within 30% of the fundamental limit. We investigate the character of the potential energy functions and resulting wavefunctions and find that a broad range of potentials yield the same intrinsic hyperpolarizability ceiling of 0.709.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
81
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(87 citation statements)
references
References 26 publications
4
81
1
1
Order By: Relevance
“…Kuzyk et al have studied a sub-problem of this, namely performing the optimization for the single-electron case with both one and two dimensional potentials. They suggest that implementing the qualitative (modulated) features observed in their optimized potentials might allow design of molecules with higher hyperpolarizabilities [4,5]. While these calculations have resulted in a number of potentials with large hyperpolarizabilities, they do not distinguish which features of the optimized potential are required for high β and which are artifacts of the minimization procedure or chosen parametrization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuzyk et al have studied a sub-problem of this, namely performing the optimization for the single-electron case with both one and two dimensional potentials. They suggest that implementing the qualitative (modulated) features observed in their optimized potentials might allow design of molecules with higher hyperpolarizabilities [4,5]. While these calculations have resulted in a number of potentials with large hyperpolarizabilities, they do not distinguish which features of the optimized potential are required for high β and which are artifacts of the minimization procedure or chosen parametrization.…”
Section: Introductionmentioning
confidence: 99%
“…In a notable series of papers, Kuzyk et al have shown [2][3][4][5] that all of the measured off-resonant first hyperpolarizabilities β zzz -specifically the second derivative of the polarization in a given direction z with respect to an electric field with vanishingly small frequency and wavevector in that direction -of known molecules are considerably smaller than a theoretical upper limit β max derived from the Thomas-Kuhn sum rules and the sum-overstates formula…”
Section: Introductionmentioning
confidence: 99%
“…We should point out that the quantum limits are obtained by assuming that the response is dominated by the contributions of three overlapping states, an ansatz that has been extensively verified numerically using Monte Carlo methods [20] as well as potential energy optimization. [21] There are no assumptions about the symmetry properties of the states. However, this does not imply that symmetry plays no role in he optimization of the second hyperpolarizability.…”
Section: Theorymentioning
confidence: 99%
“…In this work, we analyze the best device materials to gain an understanding of the amount of future improvements that are attainable by invoking the fundamental limits of the nonlinear-optical response of the hyperpolarizability. [24,25] Until a recent breakthrough in molecular design using modulation of conjugation (MOC), [26,27,28] the best molecules fell a factor of 30 short of the fundamental limit. [29] II.…”
Section: Introductionmentioning
confidence: 99%